Histological and molecular characterization of the growing nasal septum in mice. Issue 3 (12th October 2020) - Baddam, Pranidhi; Kung, Tiffany; Adesida, Adetola B.; Graf, Daniel
Abstract: The nasal septum is a cartilaginous structure that serves as a pacemaker for the development of the midface. The septum is a hyaline cartilage which is surrounded by a perichondrium and epithelium. It remains cartilaginous anteriorly, but posteriorly it undergoes endochondral ossification to form the perpendicular plate of the ethmoid. Understanding of hyaline cartilage differentiation stems predominantly from investigations of growth plate cartilage. It is currently unclear if the morphological and molecular properties of the differentiating nasal septum align with what is known from the growth plate. In this study, we describe growth, molecular, and cellular characteristics of the nasal septum with reference to hyaline cartilage differentiation. The nasal septum grows asynchronous across its length with phases of rapid growth interrupted by more stagnant growth. Growth appears to be driven predominantly by acquisition of chondrocyte hypertrophy. Similarly, cellular differentiation is asynchronous, and differentiation observed in the anterior part precedes posterior differentiation. Overall, the nasal septum is structurally and molecularly heterogeneous. Early and extensive chondrocyte hypertrophy but no ossification is observed in the anterior septum. Onset of hypertrophic chondrocyte differentiation coincided with collagen fiber deposition along the perichondrium. Sox9, Col2, Col10, Mmp13, Sp7, and Runx2 expression was heterogeneous and did not always follow the expected pattern established from chondrocyte differentiation in the growth plate. The presence of hypertrophic chondrocytes expressing bone‐related proteins early on in regions where the nasal septum does not ossify displays incongruities with current understanding of hyaline cartilage differentiation. Runx2, Collagen II, Collagen X, and Sp7 commonly used to mark distinct stages of chondrocyte maturation and early bone formation show wider expression than expected and do not align with expected cellular characteristics. Thus, the hyaline cartilage of the nasal septum is quite distinct from growth plate hyaline cartilage, and caution should be taken before assigning cartilage properties to less well‐defined cartilage structures using these commonly used markers. Beyond the structural description of the nasal cartilage, this study also provides important information for cartilage tissue engineering when using nasal septal cartilage for tissue regeneration. Abstract : The nasal septum is a heterogeneous cartilage with differential location‐dependent growth characteristics. Hypertrophic chondrocytes are found throughout the septum, although endochondral ossification is restricted to the posterior region. Columnar and hypertrophic chondrocytes are not sequentially organized as in growth plates. Hypertrophy appears to be a significant component in septum growth. Osteocalcin may reflect metabolic requirements rather than a particular chondrocyte maturation stage.